Sistemas de controle fuzzy neural e neural adaptativo destinados ao controle de pressão em rede de distribuição de água - Moura, Geraldo de Araújo (2016)
This work deals with pressure control in water distribution networks to promote the optimization of hydraulic loads in order to minimize water losses in the pipes and energy in the corresponding pumping system. Therefore, a neural fuzzy control system (NFCS) beyond the adaptive neural control system (ANCS) were developed. These control systems have been tested and evaluated on experimental bench. The neural fuzzy control system (NFCS) involves techniques of artificial neural network (ANN) and fuzzy logic. The adaptive neural control system (ANCS) used a ANN Perceptron type multilayer by backpropagation technique and gradient descent with Levenberg-Marquardt optimizer. The pressure control will be through the frequency inverter with frequency adjustments in real time, which will act on pump motor assembly installed in the trial bench hydraulic network. Control systems NFCS and ANCS, in this work, were confronted in order to promote a comparative analysis between controllers. The results showed that the ANCS reached a performance index greater than NFCS almost entirely. Finally it was added a logic filter to supervisory control and data acquisition system (SCADA) to make the ANCS able to alternately control the minimum pressure points from the distribution network of experimental bench. Both control systems, ANCS and NFCS were developed in programming environment LabVIEW®